Voices of change: public narrative storytelling communicates climate resilience actions in Kenya - Ng'endo, Mary; Kariuki, Esther (Taylor & Francis Group, 2025)
Powerful stories can inspire people to take action on climate change by using relatable lived experiences people connect with. In the “Voices of Change” project, the CGIAR Research Initiative on Climate Resilience (ClimBeR) partnered with a local non-governmental organisation leading climate-resilient advocacy in Kenya, the Centre for Minority Rights Development (CEMIRIDE), to amplify community stories of climate adaptation. Our study used public narrative storytelling, employing a three-part “story of self, story of us, story of now” framework. Public narrative storytelling incorporates people’s personal stories with those of others, connecting storylines to clear policy and call-to-action goals. Our study demonstrated how Indigenous communities can bring their experience of what works in a local context to decision makers, and how doing so may successfully lead to a better match between local ideas (which align with national priorities) and global priorities on climate adaptation, thus showing the importance of local knowledge at global level.